2004
DOI: 10.1089/scd.2004.13.625
|View full text |Cite
|
Sign up to set email alerts
|

Transient Differentiation of Adult Human Bone Marrow Cells into Neuron-like Cells in Culture: Development of Morphological and Biochemical Traits Is Mediated by Different Molecular Mechanisms

Abstract: Studies on rodent bone marrow stromal cells (MSCs) have revealed a capacity, for at least a portion of cells, to express neuron-like traits after differentiation in culture. Little, however, is known about the ability of human MSCs in this regard. We show here that incubation with certain differentiation cocktails, particularly those that include reagents that increase cellular cAMP levels, produces a rapid (1-4 h) and transient (24-48 h) transformation of nearly all hMSCs into neuron-like cells displaying a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 44 publications
(65 reference statements)
1
43
1
Order By: Relevance
“…These include retinoic acid (Cho et al, 2005), DMSO and BHA (Chu et al, 2004;Lu et al, 2004), GM1 and bFGF (Dezawa et al, 2004;Zhang et al, 2004b;Munoz-Elias et al, 2003), and 2-mercaptoethanol (2-ME) (Guo et al, 2001). It was suggested that cAMP signaling pathway should be involved in neurocytic differentiation of MSCs (Suon et al, 2004;Jori et al, 2005), but it could not rule out the synergistic effect of other signaling pathways on neurogenesis of hMSCs, in regard to neural differentiation of embryonic stem cells (Kleber et al, 2005;Bainter et al, 2001;Otero et al, 2004). Neuhuber et al(2004) highlighted the possible deficiencies of many protocols for differentiating MSCs into neurocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These include retinoic acid (Cho et al, 2005), DMSO and BHA (Chu et al, 2004;Lu et al, 2004), GM1 and bFGF (Dezawa et al, 2004;Zhang et al, 2004b;Munoz-Elias et al, 2003), and 2-mercaptoethanol (2-ME) (Guo et al, 2001). It was suggested that cAMP signaling pathway should be involved in neurocytic differentiation of MSCs (Suon et al, 2004;Jori et al, 2005), but it could not rule out the synergistic effect of other signaling pathways on neurogenesis of hMSCs, in regard to neural differentiation of embryonic stem cells (Kleber et al, 2005;Bainter et al, 2001;Otero et al, 2004). Neuhuber et al(2004) highlighted the possible deficiencies of many protocols for differentiating MSCs into neurocytes.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can acquire neuron-like phenotypes through a twostage process including early morphological changes and the later biochemical induction of neuron-specific genes, which appear to be mediated by independent pathways [9]. In this study, we investigated the signaling molecules responsible for induction of neuron-like phenotypes in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that short-term treatment with b-mercaptoethanol and dimethylsulfoxide caused rapid rearrangement of the actin cytoskeleton and thereby similar morphological changes in fibroblastic cells [7,8]. In fibroblastic cells, however, the rapid morphological changes were not followed by expression of neuronal markers at the mRNA or protein level [7,8], whereas neuron-specific proteins were induced in MSCs by de novo gene transcription [9]. Thus, the early morphological and the later biochemical changes in MSCs appear to be mediated by independent pathways and/or mechanisms during acquisition of neural traits by MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Further differentiation of DA traits in Stage V was achieved by incubating cells seeded onto poly-ornithine coated slides for an additional 1-7 days in DM supplemented with 1mM dibutyryl cAMP (dbcAMP) as described in earlier studies (20,23,24). Following this treatment, no cells expressed stem cell markers like Oct-4 ( Fig.…”
Section: Additional Da Differentiationmentioning
confidence: 99%